Analysis of DGS filters using π‐circuit model. Issue 7 (2nd June 2020) - Malhotra, Sambhav; Hashmi, Mohammad
Abstract: The design and analysis of two defected ground structures (DGS)‐based filters have been proposed in this article. The first is a multifrequency bandstop filter (BSF) which utilizes a semi‐H defect in the ground plane. This structure is then prototyped on a Rogers 4350B substrate of overall size 45 mm × 15 mm with an external SMD capacitors employed to control the resonance of the circuit for the stopband frequencies of 433, 700, and 915 MHz. An equivalent π ‐circuit is modified to validate this multiband filter. The second filter is a combination of a BSF and bandpass filter in one structure. The filter operating with a controllable passband and stopband frequency is fabricated on Rogers 4350B lossy substrate. Two SMD capacitors are loaded in the filter structure to control the passband and stopband frequencies of the filter with a structure size of 20 mm x 20 mm. Finally, the equivalent circuit from the BSF is modified further to encompass the bandpass and bandstop frequency response of the proposed work. Abstract : This article analyzes a multiband stopband filter made from DGS using a π type circuit model. This circuit model is then modified to include a bandpass response of a DGS based bandpass/bandstop filter.